Traction Synchronous Machine with Rotor Field Winding and Two-Phase Harmonic Field Exciter - Vladimir Prakht; Vladimir Dmitrievskii; Vadim Kazakbaev; Aleksey Paramonov; Victor Goman (World Electric Vehicle Journal)
Many modern electric drives for cars, trucks, ships, etc., use permanent magnet synchronous motors because of their compact size. At the same time, permanent magnets are expensive, and their uncontrolled flux is a problem when it is necessary to provide a wide constant power speed range in the field weakening region. An alternative to permanent magnet motors is synchronous motors with field windings. This article presents a novel design of a traction brushless synchronous motor with a field winding and a two-phase harmonic exciter winding on the rotor and zero-sequence signal injection. The two-phase harmonic exciter winding increases the electromotive force on the field winding compared to a single-phase one and makes it possible to start the motor at any rotor position. This article discusses the advantages of the proposed design over conventional solutions. A simplified mathematical model based on the finite element method for steady state simulation is presented. The machine performance of a hysteresis current controller and a field-oriented PI current controller are compared using the model.